The Contribution of Islamic Sciences Reasoning in Strengthening Religious Moderation in Indonesia - Mukti, Abdul; Askar, Romlah Abubakar; Salim, Delmus Puneri; Rosdiawan, Ridwan; Duraesa, M. Abzar; ., Ihsan (Journal of Posthumanism, 2025)
This study focuses on discussing the model of reasoning that develops in Islamic sciences on the one hand and its contribution to strengthening the concept and paradigm of religious moderation which is currently being developed as an effort to build civilization in Indonesia as a pluralistic country. The focus of this study asks research questions, namely, (1) How is the relationship between the reasoning of Islamic sciences and the conception of religious moderation?; (2) What is the contribution of the reasoning of Islamic sciences to the conception of religious moderation? This study is a library study that relies on data in the form of literature documents such as literature books, manuscripts, journals, and articles. This study is approached with a hermeneutic approach with descriptive analysis. This study found that the reasoning of Islamic sciences such as bayani, burhani, and irfani contribute positively intellectually in strengthening the concept and paradigm of religious moderation. All three contribute methodological sides in the form of textual arguments, logical arguments, and intuition arguments in strengthening religious moderation.